2020
DOI: 10.1089/jwh.2019.7850
|View full text |Cite
|
Sign up to set email alerts
|

Increased Likelihood of Pregnancy Using an App-Connected Ovulation Test System: A Randomized Controlled Trial

Abstract: Background: Women trying to conceive are increasingly using fertility-tracking software applications to time intercourse. This study evaluated the difference in conception rates between women trying to conceive using an application-connected ovulation test system, which measures urinary luteinizing hormone and an estrogen metabolite, versus those trying without using ovulation testing. Materials and Methods: This home-based study involved 844 volunteers aged 18-40 years seeking to conceive. Volunteers randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Indeed, 65% of cycles range between 25 and 30 days in length, and a further 7-8.5% of women experience cycles over 35 days in length (Bull et al, 2019b;Grieger & Norman, 2020). In studies where the focus was conception, participants were recruited only if they had 'just started' trying to conceive (Faust et al, 2019), or had been trying for <6 months (or if aged over 35 years, <3 months) (Johnson et al, 2020). A potential bias is thus created, limiting the both participation and applicability of findings to people outside of this range.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 65% of cycles range between 25 and 30 days in length, and a further 7-8.5% of women experience cycles over 35 days in length (Bull et al, 2019b;Grieger & Norman, 2020). In studies where the focus was conception, participants were recruited only if they had 'just started' trying to conceive (Faust et al, 2019), or had been trying for <6 months (or if aged over 35 years, <3 months) (Johnson et al, 2020). A potential bias is thus created, limiting the both participation and applicability of findings to people outside of this range.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we find that anovulation Though the body of existing data on the impact of timed intercourse is insufficient to draw conclusions, 35 recent observational studies and a trial in couples trying to conceive suggest that timing of intercourse to the fertile window using fertility indicators result in higher fecundability independent of coital frequency, further highlighting the importance of intercourse timing. [36][37][38] A recent study that found that double intrauterine insemination with donor sperm did not increase ongoing pregnancy rates in women without a history of infertility provides additional evidence supporting that increasing frequency matters to cover the fertile window, but does not improve pregnancy rates once the fertile window is already attained. 39 Our simulation supports the principle that unscheduled regular intercourse, averaging every other day, will greatly increase the chances of intercourse occurring within the fertile window, which will, in turn, improve time to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…39 Our simulation supports the principle that unscheduled regular intercourse, averaging every other day, will greatly increase the chances of intercourse occurring within the fertile window, which will, in turn, improve time to pregnancy. However, for a variety of personal reasons, some couples of normal fecundity 35,37,38 may find timing of intercourse to the fertile window a more acceptable approach to increase fecundability, for example among women who experience pain with intercourse. An additional caveat for the strategy of frequent unscheduled intercourse is that one study has suggested that frequent intercourse in the peri-implantation time window may reduce fecundability, 40 though this finding has not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have demonstrated that compared to the LMP, early pregnancy dating based on the self‐reported urinary LH surge more closely correlates with the CRL. Since urinary LH testing is Food and Drug Administration approved, is readily available over the counter, and has been shown to increase the likelihood of conceiving per cycle, 16 perhaps providers should encourage its use and use the self‐reported date of the urinary LH surge for estimation of GA.…”
Section: Discussionmentioning
confidence: 99%